The role of schools in the implementation of tolerant characteristics in smp negeri 1 purwakarta - Abiyuna, Thaufan (Universitas Tanjungpura, 2024)
Diversity is the face of Indonesia that is seen by the world. The real differences have a good impact if the development of tolerance is carried out in its education system. In this case, schools play a strategic role in becoming the leading institution that encourages the strengthening of tolerance values as is done at SMP Negeri 1 Purwakarta. This study aims to analyze the role of schools in implementing Character Education in Purwakarta, especially in building tolerant characters. Through the case study method, this study involved teachers, students, school committees, and parents. The results of the study show that SMP Negeri 1 Purwakarta plays a role in (1) implementing every technical rule; (2) providing facilities and infrastructure to support every Character Education program; (3) striving to create an educational environment that is free to worship and has no restrictions whatsoever; (4) a party that strives to build tolerance in several educational bases; and (5) as a place to train students' characters to improve the quality of graduates.